Actinic keratoses show variable histological basal growth patterns – a proposed classification adjustment. (16th October 2017) - Schmitz, L.; Gambichler, T.; Gupta, G.; Stücker, M.; Stockfleth, E.; Szeimies, R.M.; Dirschka, T.
Abstract: Background: Common histological classification schemes of actinic keratoses (AK) do not evaluate growth patterns at basal epidermal aspects of AK. Until now, the importance of basal epidermal growth patterns of AK has not been studied. Objective: To investigate the extent of atypical keratinocytes throughout the epidermis and variation in basal growth patterns of AK. Methods: AK lesions occurring on the head/face from patients seen in routine practice were assessed histologically. We determined histological grade (AK I‐III), basal growth patterns of atypical keratinocytes (crowding, budding and papillary sprouting) and accompanying parameters. Results: Of the 246 lesions included, 28.0% were histologically classified as AK I, 46.7% as AK II and 25.2% as AK III. Approximately 26.4% of the basal growth patterns were classified as crowding (pro I), 49.6% as budding (pro II), 17.9% as papillary sprouting (pro III) and 6.1% without basal directed growth. No significant correlation of the histological AK I‐III grading and underlying growth patterns was observed ( P = 0.4666). However, adnexal structure involvement (OR = 2.37; 95% CI 1.21–4.65), infiltration (OR = 2.53; 95% CI 1.31–4.90) and increased number of vessels (OR = 2.56; 95% CI 1.42–4.65) were independent positive predictive markers for pro II and pro III basal growth patterns. Conclusions: Basal growth patterns (pro I‐III) in AK do not correlate with the established AK I‐III histological grading system. Besides the degree of upward extension, varying degrees of downward extension exist. Histological classification should consider both, upwards and downward growth patterns when assessing AK.